Pedagogical Hope - Raquel Ayala Carabajo (Phenomenology & Practice, 2013)
This paper explores the experience of pedagogical hope from educators’ viewpoints. Starting from a multidisciplinary study, it has been developed through the collection and analysis of descriptions of experiences lived by educators, which have revealed some essential points: realism, sense of wonder, patience, and openness, among others. The discovery of the powerful and fundamental influence of hope in the lives of teachers exercising their role, assistants, school counselors, as well as in the lives of the children and youth whom they have been entrusted, leads us to preserve and attest to it.